Application of Fluorescent Cholangiography for Determination of the Resection Line During a Single-Incision Laparoscopic Cholecystectomy for a Benign Lesion of the Cystic Duct: Preliminary Experience. Issue 6 (December 2016) - Nojiri, Motoi; Igami, Tsuyoshi; Tanaka, Hiroshi; Toyoda, Yoshitaka; Ebata, Tomoki; Yokoyama, Yukihiro; Sugawara, Gen; Mizuno, Takashi; Yamaguchi, Junpei; Nagino, Masato
Abstract : Background: To avoid bile leakage from the stump of a cystic duct that is closed at edematous and/or involved areas, the decision regarding the location of the resection line during a laparoscopic cholecystectomy for benign lesions extending into the cystic duct is important and requires technical ingenuity. For these situations, we used fluorescent cholangiography. Methods: Our procedure for single-incision laparoscopic cholecystectomy utilized the SILS-Port, and an additional pair of 5-mm forceps was inserted via an umbilical incision. As a fluorescence source, 1 mL of indocyanine green was intravenously injected after endotracheal intubation of patients in the operating room. A laparoscopic fluorescence imaging system developed by Karl Storz Endoskope was utilized for fluorescent cholangiography. Results: Fluorescent cholangiography could be used to identify the border of the lesion in the cystic duct. According to the fluorescent cholangiography results, a location for the resection line of the cystic duct could be identified; therefore, the planned resection was successful and produced a histologically negative margin. Conclusions: Application of fluorescent cholangiography in the determination of the location of the resection line location during a laparoscopic cholecystectomy for benign lesions of the cystic duct should be widely accepted.